The “Elephant in the Room”: Why and How Medium of Instruction and Decolonisation of Education are Linked - van Pinxteren, Bert (Journal of Contemporary Issues in Education, 2022)
The content of education and the medium in which it is delivered are generally seen as two different things: a curriculum that is in need of being “decolonised” can still be delivered in a colonial language. Likewise, a curriculum that is colonial in nature could in theory be delivered in any medium of instruction. This article argues that, seen from a macro perspective, this belief is incorrect. In African settings (and probably elsewhere as well), the medium of instruction and the content of that instruction are intricately linked. Evolution towards a decolonial educational system has to include a change in the medium of instruction if it is to be successful.